2003
DOI: 10.1093/ajcn/78.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of dried peas with those of potatoes in mixed meals on postprandial glucose and insulin concentrations in patients with type 2 diabetes

Abstract: These findings suggest that carbohydrates in dried peas may be largely disregarded in carbohydrate counting and that type 2 diabetic patients should probably increase their consumption of low-glycemic, high-fiber foods at the expense of high-glycemic, low-fiber foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…Liljeberg et al (1999) reported that some low-GI breakfasts could improve glucose tolerance at a subsequent lunch. The higher insulin levels observed after the white wheat flour in this study is consistent with most of the studies using simple Effects of meals with barley or wheat on satiety JB Keogh et al sugars or carbohydrate-rich foods as the test meals (Holt and Brand-Miller, 1995;Lavin and Read, 1995;Ludwig, 2002;Schafer et al, 2003). Ludwig et al (1999) have suggested that meals with different GI may have markedly different effects on the metabolic response.…”
Section: Discussionsupporting
confidence: 90%
“…Liljeberg et al (1999) reported that some low-GI breakfasts could improve glucose tolerance at a subsequent lunch. The higher insulin levels observed after the white wheat flour in this study is consistent with most of the studies using simple Effects of meals with barley or wheat on satiety JB Keogh et al sugars or carbohydrate-rich foods as the test meals (Holt and Brand-Miller, 1995;Lavin and Read, 1995;Ludwig, 2002;Schafer et al, 2003). Ludwig et al (1999) have suggested that meals with different GI may have markedly different effects on the metabolic response.…”
Section: Discussionsupporting
confidence: 90%
“…The possible differences between the two types of peas should be investigated with larger study populations and perhaps with larger food portions. Consideration should be given to the inclusion of peas as a recommended snack food 33 …”
Section: Discussionmentioning
confidence: 99%
“…Slowly digestible carbohydrate meals result in lower postprandial glucose and lipid levels than diets with readily available carbohydrate [187][188][189]. There is a definite advantage in eating carbohydrates with a high fiber content [190][191][192].…”
Section: Diet and Physical Activitymentioning
confidence: 99%